Proceedings of the 5th International Conference on Community Development (AMCA 2018) 2018
DOI: 10.2991/amca-18.2018.97
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sharia Supervisory Board Characteristics on the Shariah Compliance

Abstract: The purposes of this study are to identify the influence of SSB Characteristics on Shariah Compliance of AAOIFI Disclosure and to examine the influence of Shariah Supervisory Board (SSB) Characteristics on Shariah Compliance of AAOIFI Disclosure related to shariah supervisory board (SSB). The population of this study comprises financial firms operating in compliance with the Shariah principles in the Indonesian islamic banking. This research concentrates on the annual report of islamic banking, although firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
1
7
1
Order By: Relevance
“…SSB experience without being supported by a broad understanding of Shari"ah governance has been able to increase the disclosure related to SSB information. Fakhruddin and Jusoh (2018), Ahmed and Khatun (2013) revealed that SSB is one independent body consisting of fiqh scholars helping themselves in fiqh muammalah or those experts in the field of Islamic financial institutions and have a complete understanding of fiqh muammalah.SSB does have experiences to test integrity and credibility similarly as the other financial professionals, including bankers, lawyers, and accountants regulated by professional bodies that certain professional ethics impose (Onagun, 2013).The finding this study does not support to Fakhruddin and Jusoh (2018) research that SSB experience does not significantly influence Shari"ah compliance.…”
Section: Discussioncontrasting
confidence: 56%
“…SSB experience without being supported by a broad understanding of Shari"ah governance has been able to increase the disclosure related to SSB information. Fakhruddin and Jusoh (2018), Ahmed and Khatun (2013) revealed that SSB is one independent body consisting of fiqh scholars helping themselves in fiqh muammalah or those experts in the field of Islamic financial institutions and have a complete understanding of fiqh muammalah.SSB does have experiences to test integrity and credibility similarly as the other financial professionals, including bankers, lawyers, and accountants regulated by professional bodies that certain professional ethics impose (Onagun, 2013).The finding this study does not support to Fakhruddin and Jusoh (2018) research that SSB experience does not significantly influence Shari"ah compliance.…”
Section: Discussioncontrasting
confidence: 56%
“…The membership of the Shariah Supervisory Board that is connected to the external environment must be able to enable the Shariah Supervisory Board to monitor externally and communicate about possible earnings management practices. The Supervisory Board Meeting must be one medium for sharing information and as a source of information about other activities and policies carried out by managers, especially regarding the presentation of financial statements [6]. However, the results of this study indicate that Shariah Supervisory Board meetings have not been effective in knowing and discussing earnings management practices that may be carried out by managers.…”
mentioning
confidence: 70%
“…Shariah Supervisory Board is a body that is given the authority to supervise/supervise and closely look at the activities of shariah financial institutions so that these institutions always follow the rules and principles of shariah [6]. SSB sees in broad terms the aspects of management and administration that must be following shariah, and most importantly, endorsing and supervising shariah banking products to comply with shariah provisions and applicable laws.…”
Section: Shariah Supervisory Board (Ssb)mentioning
confidence: 99%
“…Rahman and Bukair (2013) finds a positive association between CSR disclosure and the SSBSCORE at five percent significance level. Fakhruddin and Jusoh (2018) found that the cross member has a positive influence on the shariah compliance disclosure. The result of this study implies that SSB cross memberships in Islamic financial institutions are effective for monitoring and controlling the Islamic banks' activities related to social issues according to both Shari'ah rules and principles.…”
Section: Discussionmentioning
confidence: 97%